Motives of pro-social behavior in individual versus collective decisions: A comparative experimental study - Ivo Bischoff; Thomas Krauskopf (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
We investigate the motives of pro-social behavior in collective decisions in an economic experiment. It compares individual behavior in private and collective decisions in a unified experimental setup. Subjects are given an individual endowment and have to decide how much of it to donate to charity. The experiment is combined with two long questionnaires that provide us with background information on subjects and enables us to learn more about the motives driving their behavior. Contrary to theoretical predictions, the distribution of amounts donated individually is remarkably similar to the distribution of amounts proposed for collective donation. In regressions, we find individual donations to be driven by consequentialist motives, social norms and moral convictions. In collective decisions, neither the motiverelated variables nor any of the control variables are found significant. Comparing subjects' affective state before and after the experiment, we find that individual donations create a feeling of warm glow while collective donations do not. On the other hand, the change in affective state in the collective decision is higher the higher the amount proposed for the collective donation. This pattern is consistent with expressive motives.
Keywords: C90; D72; 330; voting motives; voluntary contributions; redistribution; charity; economic experiment; warm-glow; Immanuel Kant; affect